Implementasi Metode Pembelajaran Mufrodat pada Pelajaran Bahasa Arab di SMP Islam Al Fadli Medan - Ummaya, Dwi Sabrina; Wirian, Oktrigana (ANWARUL, 2024)
This study aims to analyze the implementation of vocabulary learning methods in Arabic language instruction at SMP Islam Al Fadli Medan. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis from five Arabic language teachers. The findings indicate that teachers employ interactive methods, such as language games, to enhance student interest. Additionally, the integration of technology, like digital learning applications, aids students in better remembering vocabulary. However, challenges such as limited resources and diverse student abilities persist. Teachers need to adjust methods to accommodate all students' needs and enhance professional training for effective teaching. In conclusion, interactive methods in vocabulary instruction have significant potential to improve the quality of Arabic language teaching. This research is expected to serve as a reference for further development in Arabic teaching at the secondary school level.